2017
DOI: 10.1055/s-0037-1603653
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Change in Uterocervical Angle is not a Risk Factor for Preterm Birth in Women with a Short Cervix

Abstract: Objective To determine if change in uterocervical angle (UCA) is associated with an increased rate of preterm birth (less than 37 weeks) for women with a short cervix. Study Design A retrospective study was performed from January 2013 to March 2016 of singleton pregnancies undergoing universal cervical length screening. The difference between the UCA for the first cervical length ≤ 2.5 cm and last recorded cervical length < 25 weeks was defined as the change in UCA. The primary outcome was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 14 publications
0
15
0
2
Order By: Relevance
“…Eleven studies were finally included in the present systematic review that evaluated data from 3,018 women (Table 1) [12–22]. Among them, 5 studies evaluated pregnancy outcomes in unselected singleton pregnancies [14, 16, 17, 21, 22], two studies reported outcomes in women with a shortened cervix that were offered cerclage [6, 21], one study evaluated changes in UCA in women with a shortened cervix that were followed up with at least two measurements of cervical length during the second trimester of pregnancy [15], two studies enrolled unselected twin pregnancies [13, 18], and one study evaluated the impact of UCA in the latency period of pregnancies complicated by PPROM [20]. The results of the Newcastle-Ottawa Scale are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies were finally included in the present systematic review that evaluated data from 3,018 women (Table 1) [12–22]. Among them, 5 studies evaluated pregnancy outcomes in unselected singleton pregnancies [14, 16, 17, 21, 22], two studies reported outcomes in women with a shortened cervix that were offered cerclage [6, 21], one study evaluated changes in UCA in women with a shortened cervix that were followed up with at least two measurements of cervical length during the second trimester of pregnancy [15], two studies enrolled unselected twin pregnancies [13, 18], and one study evaluated the impact of UCA in the latency period of pregnancies complicated by PPROM [20]. The results of the Newcastle-Ottawa Scale are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning delivery prior to 28 weeks the optimal performance of the ROC analysis was observed at 112° with a sensitivity of 100% and a specificity of 62%. Finally, Lynch et al evaluated women that were sequentially screened during the second trimester of pregnancy and observed that the difference in UCA among these measurements was not able to predict preterm birth [15]. However, they did mention that a final UCA of ≥105° prior to 25 weeks of gestation was associated with an increased risk of preterm birth <34 weeks (24.2% versus 6.8%, p=.01 ).…”
Section: Resultsmentioning
confidence: 99%
“…Una investigación retrospectiva encontró que un valor mayor o igual a 105º entre las 19 y 24 semanas de gestación estaba relacionado con una menor incidencia de PP antes de las 34 semanas. Sin embargo, los autores incluyeron a embarazadas con LC corta (12) . Otra investigación halló que el valor de la COR era de 0,704 y el valor de corte optimo era de 110º, con sensibilidad de 83% y valor predictivo positivo de 16%.…”
Section: Discussionunclassified
“…Un AUC agudo refuerza el cierre del canal endocervical, mientras que un ángulo más obtuso puede facilitar la apertura del cuello uterino. Varios estudios han analizado la capacidad de predicción de esta medición (9)(10)(11)(12)(13)(14) . Sin embargo, la mayoría de los estudios han sido retrospectivos y ninguno ha comparado este marcador con la LC en la predicción de parto inminente en pacientes con amenaza de PP.…”
unclassified
“…Some parameters have been investigated in previous studies. These include cervical length (CL; measured by transvaginal ultrasonography), cervical stiffness (measured by elastography), angle of progress, and posterior cervical angle [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%